2015
DOI: 10.1103/physrevlett.115.086601
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-Dominated Pure Spin Current Transport inAlq3Molecules

Abstract: We address the controversy over the spin transport mechanism in Alq 3 utilizing spin pumping in the Y 3 Fe 5 O 12 /Alq 3 /Pd system. An unusual angular dependence of the inverse spin Hall effect is found. It, however, disappears when the microwave magnetic field is fully in the sample plane, excluding the presence of the Hanle effect. Together with the quantitative temperature-dependent measurements, these results provide compelling evidence that the pure spin current transport in Alq 3 is dominated by the exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 56 publications
8
57
0
1
Order By: Relevance
“…Furthermore, Fig. 3c shows that the peak field of the DC-voltage increased with the frequency that fits well with the Kittel formula 29,30 , f=( γ /2 π )(H res *(H res +4 π M s )) 1/2 , with the gyromagnetic ratio γ = gμ B /h=1.738×10 11 T −1 s −1 and the saturation magnetization M s =0.248 T. It gave a Lander factor g=2.08 for magnetized Pt surface. The fitted M s of magnetized Pt is very closed to the observed value in Ni/Pt system by XMCD measurement 19 .…”
Section: Yig(16nm)/pt(10nm) Systems the Black Circles Insupporting
confidence: 72%
“…Furthermore, Fig. 3c shows that the peak field of the DC-voltage increased with the frequency that fits well with the Kittel formula 29,30 , f=( γ /2 π )(H res *(H res +4 π M s )) 1/2 , with the gyromagnetic ratio γ = gμ B /h=1.738×10 11 T −1 s −1 and the saturation magnetization M s =0.248 T. It gave a Lander factor g=2.08 for magnetized Pt surface. The fitted M s of magnetized Pt is very closed to the observed value in Ni/Pt system by XMCD measurement 19 .…”
Section: Yig(16nm)/pt(10nm) Systems the Black Circles Insupporting
confidence: 72%
“…The employed fields of 10–400 mT (refs 19, 20) are on the same order or smaller than in ESR measurements. In the presence of an external field one must distinguish between longitudinal and transverse spin relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…Watanabe et al first reported the observation of the Hanle effect in molecular materials in a pure‐spin‐current‐type device according to the relationship between the out‐of‐plane angle (referring to the angle between the external magnetic field and the substrate plane) and the simultaneously measured values of inverse spin Hall effect (ISHE) voltage (Figure b) . However, in a later study, Jiang et al proposed that the observed “Hanle effect” may originate from the nonuniformity of the microwave magnetic field . Their conclusion has also been supported by a recent report from Yu .…”
Section: Pure‐spin‐current‐type Molecular Spintronic Devicesmentioning
confidence: 89%
“…Presently, a spin pumping process is normally employed to inject pure spin current into the molecular matrix; effectively excluding the problem of conductance mismatch between the FM and the molecules ( Figure a) . Besides the potential applications on efficient information transport, a few recent studies have also demonstrated that the pure‐spin‐current‐type molecular spintronic device is a perfect platform to study the physics of spintronic processes and spin‐related properties of molecules …”
Section: Pure‐spin‐current‐type Molecular Spintronic Devicesmentioning
confidence: 99%
See 1 more Smart Citation